TRANSFORMASI TRADISI KEILMUAN DALAM ISLAM: MELACAK AKAR KEMUNCULAN DAN PERKEMBANGAN INSTITUSI PENDIDIKAN ISLAM - Saefuddin Masyhuri (Hunafa: Jurnal Studia Islamika, 2007)
This article deals with transformation of Islamic education in the early period, that is from the epoch of the prophet Muhammad to that of the Abbasid. In the period of Mahmud, Islamic education activity took place in its simple form, centered on the companions residents. In the epoch of Khulafa’ ar-Rasyidun, mosques were used for Islamic education activity. In the epoch of Abbasid, because Muslims’ need in Islam education developed, the traditional institution of Islamic education transformed into madrasahs of their own various levels. Kata Kunci: Transformasi keilmuan Islam, perkembangan institusi, pendidikan Islam